Impact of the COVID-19 pandemic on emergency hospital cancer admissions in a UK region - Helen Mitchell; Ben S. Alford; Simon O’Hare; Eamon O’Callaghan; Colin Fox; Anna T. Gavin (BMC Cancer, 2022)
Abstract Background The pandemic disrupted society and health services through lockdowns and resource reallocation to care for COVID-19 patients. Reductions in numbers of cancer patients having surgery, being diagnosed pathologically or via 2-week wait, and screening programs pauses have been described. The effect on emergency presentation, which represents an acute episode with poor outcomes, has not been investigated. This study explored the pandemic’s impact on emergency hospital admissions for cancer patients in a UK region. Methods Hospital discharge data for cancer patients in Northern Ireland, which included route to admission, were analysed for the pandemic era in 2020 compared to averages for March to December 2017–2019, focusing on volume and route of emergency admissions by demography and tumour site. Findings Compared with the pre-pandemic era, the number of cancer emergency admissions fell by 12·3% in 2020. Emergency admissions for cancer were significantly reduced when COVID-19 levels were highest (− 18·5% in April and − 16.8% in October). Females (− 15·8%), urban residents (− 13·2%), and age groups 0 to 49 and 65–74 years old (− 17%) experienced the largest decreases as did those with haematological (− 14·7%), brain and CNS (− 27·9%), and lung cancers(− 14·3%). Significant reductions in referrals from outpatient departments (− 51%) and primary care (− 43%) (p < 0·001) were counterbalanced by admissions from other routes including confirmed or suspected COVID-19 infection (increase 83·6%). Interpretation Reductions in emergency admissions, and pathologically diagnosed cancers, as reported by the Northern Ireland Cancer Registry (NICR), indicate undiagnosed patients in the community which has implications for future workloads and survival. Data suggest undiagnosed cases may be higher for haematological, brain and CNS, and lung cancers and among females. Efforts should be made to encourage people with symptoms to present for diagnosis or reassurance. Funding The NICR is funded by the Public Health Agency of Northern Ireland. This work was supported by Macmillan Cancer Support and uses data collected by health services as part of their care and support functions.